A revision of the genus Renealmia (Zingiberaceae) in Tropical Africa. I. New species from Central Africa (Cameroon, Rio Muni, Gabon, Democratic Republic of the Congo), and notes on the identity of Renealmia africana, R. congolana, and R. dewevrei - Fischer, Eberhard; Dhetchuvi, Jean-Baptiste M.m. (Phytotaxa, 2024)
Ten new species of Renealmia from tropical Africa are described, among them one from Cameroon (R. tenuispica), one from Rio Muni (Equatorial Guinea), Gabon and D.R. Congo (R. ewangoi), four from Gabon (R. longicarpa, R. longituba, R. tchimbeleana, R. tenuis), and four from D.R. Congo (R. botsimana, R. longispicata, R. montana, R. vermoeseniana). For each new species a preliminary conservation assessment is provided. The synonymy of Renealmia africana and R. congolana is clarified, and R. dewevrei is reinstated as a distinct species. From the three syntypes of Renealmia africana a lectotype is chosen.